The Variability of Expectations in Hyperinflations - Khan, Mohsin S. (Journal of Political Economy, 1977)
A problem in the use of adaptive expectations as a mechanism for generating expectations of inflation is the assumption that the speed with which individuals revise their expectations is constant. The purpose of this paper is to estimate the Cagan model of the demand for money for six hyperinflation countries allowing the coefficient of expectations (which measures the response to the error between the actual and the expected rate of inflation) to vary with the level and the change in the rate of inflation. The results indicate considerable support for this particular hypothesis.